Bioaccumulation of heavy metals in mackerel and red hybrid tilapia collected from Kijal and Paka, Terengganu, Malaysia - Dabwan, Ahmed H. A.; Saluddin, Ummu Asma? Hafifah Bt. Mohmad; Isa, Nursuhaili Bt. Mohd; Abdullah, Abdul Hadi; Mohamed, Amri Bin Hj.; Ahmad, Anuar Bin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The major goal of this study is to determine the bioaccumulation of heavy metals in the tissues and bones of Red Hybrid Tilapia (Oreochromis niloticus) and Mackerel (Rastrelliger kanagurta) taken from two distinct sites in Terengganu state, Malaysia, namely Kijal and Paka. Zinc (Zn), copper (Cu), nickel (Ni), and lead (Pb)were the metals examined. Soil analysis also was carried out for the same elements. The tissues and bones of the fishes were separated before further analysis was made.
Keywords: heavy metals; biomonitoring; oreochromis niloticus; metale ciężkie; ekosystem morski